1978
DOI: 10.1152/ajprenal.1978.235.3.f180
|View full text |Cite
|
Sign up to set email alerts
|

Antidiuretic hormone increases renal prostaglandin synthesis in vivo

Abstract: Studies demonstrating the antagonism by prostaglandins (PGs) of antidiuretic hormone (ADH) action led to the proposal that renal medullary PGs may act to attenuate the physiologic effects of ADH via a negative-feedback loop. Therefore, we examined urinary PG excretion, an indicator of renal PG synthesis, in rats with hereditary diabetes insipidus (DI) utilizing gas chromatography-mass spectrometry. The DI rats, devoid of ADH, excrete much less prostaglandin E2 (PGE2) than normal Long-Evans rats (39 +/- 5 vs. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0
1

Year Published

1979
1979
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 0 publications
2
27
0
1
Order By: Relevance
“…Vasopressin is another vasoconstrictor peptide that activates phospholipase A2 and releases AA (31). Previous studies have established that vasopressin stimulates the formation of PGE 2 in mesangial and tubular epithelial cells and increases the urinary excretion of PGE 2 (20,44,46). PGE 2 modulates both the tubular and vascular responses to vasopressin (9,15,38).…”
Section: Discussionmentioning
confidence: 99%
“…Vasopressin is another vasoconstrictor peptide that activates phospholipase A2 and releases AA (31). Previous studies have established that vasopressin stimulates the formation of PGE 2 in mesangial and tubular epithelial cells and increases the urinary excretion of PGE 2 (20,44,46). PGE 2 modulates both the tubular and vascular responses to vasopressin (9,15,38).…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that DI rats present reduced in vivo synthesis of PGEj and PGF^. 16 Thus, probably the absence of hyperfiltration in remnant nephrons in DI rats was due to the lack of ADH, a diminished synthesis of PGs, or both. The present data suggest that reduction of renal mass associated with systemic hypertension enhances the adaptive mechanisms of the remnant nephron due to intrarenal vasodilation and an increase in K t that, ultimately, causes hyperfiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the toad bladder by Zusman et al (23) (24,25). That DDAVP, a vasopressin analogue that lacks pressor activity, has the same effect strongly suggests that it is the antidiuretic property of vasopressin that is important in this respect (25).…”
Section: Discussionmentioning
confidence: 99%